THE INFLUENCE OF LEARNING STYLES DURING THE PANDEMIC PERIOD ON LEARNING OUTCOMES IN ISLAMIC RELIGIOUS EDUCATION OF STUDENTS AT SDN 140 LAMPUAWA, NORTH LUWU REGENCY (International Conference on Social and Islamic Studies, 2022)
This thesis examines "The Influence of Learning Styles During the Pandemic on Learning Outcomes of Islamic Religious Education of Students at SDN 140 Lampuawa, North Luwu Regency" which aims to: 1) determine the learning styles of students during the pandemic at SDN 140 Lampuawa, North Luwu Regency; 2) to reveal the learning outcomes of Islamic Religious Education students at SDN 140 Lampuawa, North Luwu Regency; 3) to determine the effect of learning styles during the pandemic on learning outcomes of Islamic Religious Education for students at SDN 140 Lampuawa, North Luwu Regency. This research is an ex-post-facto type of quantitative research which consists of two variables, namely the learning style variable (X) and the learning outcome variable (Y). The population in this study were all students at SDN 140 Lampuawa, North Luwu Regency, totaling 127 students, while the sample was class V, totaling 25 students. The instrument used in data collection was a questionnaire used to obtain learning style data and documentation was used to obtain data on Islamic Religious Education learning outcomes. The data analysis technique used in this research is descriptive and inferential analysis. Through the two data analysis techniques above, the results of the study showed that the results of the research by the researchers obtained tcount = 4.913 and ttable = 2.069. So that tcount > ttable is 4.913 > 2.069 and the sig. 0.000 < 0.05 then HI is accepted. So it can be concluded that learning styles during the pandemic had an effect on the learning outcomes of Islamic Religious Education students at SDN 140 Lampuawa, North Luwu Regency. The implications of this research are: 1) educators as subjects in education especially in learning should be able to understand the learning styles of students in the learning process so that effective and efficient learning objectives can be achieved. 2) for fifth grade students at SDN 140 Lampuawa, North Luwu Regency, so that they can understand their abilities and potential so that they can develop quickly in order to increase learning outcomes. 3) for the principal of SDN 140 Lampuawa, North Luwu Regency, to always pay more attention to students so that they are able to learn according to their individual learning styles.